Improving quality attributes of refrigerated prepared pork chops by injecting l-arginine and l-lysine solution. (January 2022) - Chen, Li; Bao, Pengqi; Wang, Yan; Hu, Yue; Fang, Hongmei; Yang, Huamei; Zhang, Bao; He, Binbin; Zhou, Cunliu
Abstract: This study investigated the effects of l -arginine and l -lysine, as well as storage duration, on the physicochemical properties, microstructure, protein oxidation, and sensory quality of prepared pork chops. The results indicated that 0.4 g/100 g l -arginine or 0.4 g/100 g l -lysine increased the pHs from 5.25 to 6.27 and 6.26, moisture content from 74.20 g/100 g–75.47 g/100 g and 75.47 g/100 g, and redness (a*) from 5.11 to 12.4 and 14.0 of uncooked pork chops, but decreased the purge loss from 2.5% to 1.07% and 1.08%, lightness (L*) from 61.7 to 46.9 and 46.8, and yellowness (b*) from 47.2 to 43.2, 45.6 of uncooked pork chops, cooking loss from 30.77% to 24.86% and 25.27% and shear force from 35.46 N to 21.84 N and 22.03 N, but enhanced the total acceptability of cooked pork chops relative to those of the control, respectively. Histological observation revealed that l -arginine or l -lysine caused the swelling of muscle fibers. l -Arginine and l -lysine could also effectively decrease total volatile basic nitrogen over a short period and inhibit protein oxidation during the entire refrigeration storage. The results suggested that l -arginine and l -lysine could potentially improve the quality attributes of prepared pork chops. Highlights: Arginine/Lysine reduced the purge loss, cooking loss, and shear force. Arginine/Lysine increased the redness but decreased the lightness and yellowness. Arginine/Lysine caused swelling of the muscle fiber. Arginine/Lysine decreased TVB-N and reduced protein oxidation.